Tracing the multiple lives of a national romantic female translator in the early Turkish Republican period: Seniha Sami Moralı - Avci Solmaz, Safiye Gul; Karadag, Ayse Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This article examines Seniha Sami Moral & imath;, a notable yet underrepresented female translator in Turkish translation history. Employing archival methodology, the study conducts a comprehensive investigation of archival documents and related sources to construct a microhistory of Moral & imath;. The aim of the study is to identify and describe her translatorial identity within the socio-cultural and political milieu in which she acted. To this end, the article first presents details about her family and life. It then presents a discussion of her early translation practices against the backdrop of the early Turkish Republican period, suggesting that she adopted a national romantic stance, which influenced her translation practices during the establishment of the new Turkish nation. Lastly, by establishing connections between her translatorial role and other professional positions, the study highlights the interconnectedness of her multiple roles in the pursuit of shaping and preserving what she saw as a unique Turkish identity, which constructs its future by drawing upon its historical foundations.
Keywords: Archival methodology; microhistory; women translators; national romanticism; early Turkish Republican period; Communication; Linguistics